2010
DOI: 10.1614/ipsm-08-107.1
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Role of Wildfire on the Occurrence and Spread of Invasive Plant Species in Wildland Areas of the Intermountain Western United States

Abstract: Fire is unlikely to be a simple, deterministic process that will result in increased rates of invasion by nonnative plants. Relative dominance of nonnative plants at any postfire site likely results from a combination of factors, including propagule pressure (aboveground and belowground), time since invasion, interspecific competition, disturbance history, rainfall patterns, soil nutrients, environmental heterogeneity, land use, plus the actual fire dynamics. Consequently, the role different factors play in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 74 publications
(237 reference statements)
0
11
0
Order By: Relevance
“…In a study of western juniper woodlands on Steens Mountain, southeastern Oregon, Bates et al (2013) found recovery of perennial herbaceous cover after burning Phase II (codominant trees with shrubs and perennial herbs) woodlands, but Phase III (dominant trees) woodlands had limited perennial herbaceous cover both before and after severe fire. We expect continued recovery of perennial herbaceous cover on our sites where cheatgrass cover is limited and residual perennials are already well adapted to the environmental conditions (Rew and Johnson 2010).…”
Section: Should Treatments Target a Specific Phase Of Infilling?mentioning
confidence: 91%
“…In a study of western juniper woodlands on Steens Mountain, southeastern Oregon, Bates et al (2013) found recovery of perennial herbaceous cover after burning Phase II (codominant trees with shrubs and perennial herbs) woodlands, but Phase III (dominant trees) woodlands had limited perennial herbaceous cover both before and after severe fire. We expect continued recovery of perennial herbaceous cover on our sites where cheatgrass cover is limited and residual perennials are already well adapted to the environmental conditions (Rew and Johnson 2010).…”
Section: Should Treatments Target a Specific Phase Of Infilling?mentioning
confidence: 91%
“…Over the past 30 years, blackbrush communities have become increasingly susceptible to wildfire due to drought and invasion by non-native annual grasses (Abella, 2009;Rew et al, 2010). Fire has long-term effects on these communities which experience little regeneration (Callison et al 1985;Abella et al, 2009).…”
Section: Background Fire and Site Descriptions And Measurement Campmentioning
confidence: 99%
“…Anthropogenic changes to ecosystems can shift community assemblages during regeneration, triggering environmental changes that influence above-and belowground dynamics (Ammondt and Litton 2012). These changes can contribute to the establishment of invasive species in the short term, but if further disturbances are minimal, the spread of an invader within an affected ecosystem may ultimately decline over the long term (Rew and Johnson 2010). On the other hand, there is limited information about overlapping effects of niche alteration and plant invasion on native communities (Didham et al 2007;Gooden and French 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance can negatively influence resource acquisition and use by native trees and saplings (Hoffmann et al 2009), increase fuel loads for wildfires, and alter understory vegetation structure (Rojas-Sandoval and Acevedo-RodrĂ­guez 2014;Hoffmann et al 2012;Cordell and Sandquist 2008;Brooks et al 2004). The process of natural regeneration after a disturbance relies on the local plant community's ability to survive in a resource-depleted ecosystem, and amidst competition from potential invasive species, before the system can regain its optimal functionality (Ammondt and Litton 2012;Rew and Johnson 2010). If implemented according to an adaptive ecosystem management framework, human-facilitated efforts to restore ecological function can provide needed support when natural regeneration seems insufficient to restore and sustain the health, productivity, and biodiversity of the system (Griscom and Ashton 2011).…”
Section: Introductionmentioning
confidence: 99%